The impact of catch-and-release on feeding responses and aggressive behavior in Nile tilapia (Oreochromis niloticus) - Camargo-dos-Santos, Bruno [UNESP]; Rossi, Vanessa Stramantinoli [UNESP]; Gonçalves, Bruno Bastos [UNESP]; Leutz, Juliane de Abreu Campos Machado [UNESP]; Giaquinto, Percilia Cardoso [UNESP]; Sabbadin Zanuzzo, Fábio [UNESP] (Taylor & Francis, 2021)
Catch-and-Release (C&R) practice may result in post-release mortality in fish. Therefore, most C&R studies have focused on endangered or highly valued target species, and less attention has been given to introduced/abundant species, which indeed are important from an ecological point of view. Nile tilapia is considered an introduced species in many areas and is a commonly caught species in recreational fisheries; therefore, understanding the impacts of C&R on tilapia is also important from an animal welfare perspective. We investigated whether C&R impacts the aggressive behavior and feeding responses of Nile tilapia, characteristics that impair the welfare and the ability of an individual to have success in its ecosystem. Surprisingly, C&R did not affect these responses, and our results suggest that Nile tilapia may be relatively more resilient to C&R, and that C&R practices may act as an additional selective force towards the ecological success of Nile tilapia as introduced species.
Keywords: aggressivity; Catch-and-release; fish behavior; oreochromis niloticus; recreational fishing; sub-lethal effects